Cumulative fatigue damage in thin aluminum films evaluated non-destructively with lasers via zero-group-velocity Lamb modes. (December 2020) - Yan, Guqi; Raetz, Samuel; Chigarev, Nikolay; Blondeau, James; Gusev, Vitalyi E.; Tournat, Vincent
Abstract: In this paper, a non-contact non-destructive evaluation of cumulative fatigue damage in 75 μ m -thick aluminum plates is conducted by using the first symmetric zero-group-velocity Lamb mode and taking benefit of its local and long-lasting resonance feature. The tested aluminum sheets are subjected to fatigue loading, in a two sides clamped compression configuration inducing buckling. For understanding the experimental observations, we propose and establish an empirically-inspired theoretical modeling based on the cumulative damage theory, completed with a finite element simulation, for comparison with the experimental measurements. The observed phenomena along fatigue cycles show the potential for the prediction of the fatigue lifetime and the quantitative assessment of different stages of the fatigue damage in solid plate structures. Good agreement is found between the proposed theory/simulation and the experiment on zero-group-velocity resonance frequency. The quality factor of zero-group-velocity resonance is also experimentally studied and compared with numerical calculations, a disagreement is observed after ∼ 30% of fatigue lifetime. This point elucidates the start time of the change of mechanical properties during the early fatigue stage and is identified as a potential path for the improvement of the proposed empirical model in the future. Graphical abstract: